Teknik Pembibitan Jati (Tectona grandis) dan Manfaatnya untuk Rehabilitasi Hutan dan Lahan (RHL) - Aryani, Evita S.; Saroinsong, Fabiola (Yayasan Bina Lentera Insan, 2026)
Forest and Land Rehabilitation (RHL) is an effort to restore the functions of degraded forests and lands through vegetative activities, one of which is tree planting. Teak (Tectona grandis) is one of the plant species with the potential to be used in RHL activities because it has high economic value, broad adaptability, and a root system capable of helping improve land conditions. This study aims to examine teak nursery techniques as well as teak planting techniques in RHL activities as an effort to support the success of land rehabilitation both ecologically and economically. This study used a descriptive qualitative method with a literature study approach supported by field experience and interviews. Secondary data were obtained from scientific journals, books, and relevant articles through Google scholar searches using the keywords teak nursery, teak nursery techniques, forest and land rehabilitation, and benefits of teak. Primary data were obtained through interviews with employees related to nursery activities, teak seedling production, and the implementation of RHL. The data were analyzed descriptively and qualitatively through the processes of selection, classification, comparison, and interpretation of information. The results of the study indicate that the success of teak utilization in RHL activities is influenced by seedling quality and proper planting techniques. Teak nursery techniques include seed treatment through scarification, sowing, pricking out, seedling maintenance, and seedlings ready for planting at the age of approximately 3-6 months. Meanwhile, planting techniques include determining the planting location and seedling type, planting at the beginning of the rainy season, arranging planting spacing from 3 x 3 meters to 5 x 5 meters, and plant maintenance through replanting, weeding, and fertilization. With proper nursery and planting techniques, teak has the potential to support the success of RHL both ecologically and economically.